Spatial relation between open landscapes and debarking hotspots by European bison (Bison bonasus) in the Rothaar Mountains (European Bison Conservation Newsletter, 2019)
In 2013, a herd of European bison (Bison bonasus; Linnaeus, 1758) was released into the forest region of the Rothaar Mountains, Germany. The species is mostly known as grazer but also browses upon shrubs, tree bark and other roughage forage. Since the reintroduction, the population of E. bison has been growing up to 19 individuals, which started to show debarking behaviour in some areas. This behaviour caused a considerable human/wildlife conflict in the Rothaar Mountains, since the debarked patches were partially situated in privately owned commercial forests, which was connected with economic losses for local foresters. In order to investigate this issue, we determined spatial factors that may be related to debarking behaviour of the E. bison in the Rothaar Mountains, Germany. After establishing a list of potential debarking drivers, we conducted a GIS analysis of the tree utilisation in coherence with the open landscape areas in the Rothaar Mountain areas. The GIS analysis showed that patches with high debarking damage appear to be located closer to artificial feeding plots than to other open landscape types. We thus conclude that there might be an association between artificial feeding plots as open landscape areas and the debarking events of the E. bison in the Rothaar Mountains. Moreover, this case study is an example of how anthropogenic factors may affect scientific research.
Keywords: European bison; debarking; habitat composition; open landscapes; reintroduction; human-wildlife conflict